Renal sinus fat is expanded in patients with obesity and/or hypertension and reduced by bariatric surgery associated with hypertension remission - Moritz, Emilia (My University, 2023)
Prevalence of obesity has extended into pandemic-like proportions in the last few decades. Obesity (body mass index (BMI) ≥30 kg/m2) leads to a myriad of complications such as hypertension, type 2 diabetes, chronic kidney disease as well as neurodegenerative diseases and different types of cancer. Based on individual tendencies, obesity related excess fat is distributed between visceral and subcutaneous adipose tissue compartments. It has been shown that visceral adipose tissue (VAT) has a greater association with the development of comorbidities compared to subcutaneous adipose tissue (SAT). Visceral adipose tissue compartments include fat around abdominal organs as well as inside sinus-like structures. The subject of interest regarding this study was to measure fat accumulation in the renal sinus, a hilum structure where blood vessels, lymph vessels and ureters enter the kidney. It is considered that fat accumulation at the renal sinus creates increased mechanical pressure against the soft venous structures, hence leading to the activation of blood pressure altering renin-angiotensin-aldosterone -system. This theory might explain at least partly the phenomenon of obesity-related hypertension. When it comes to remission from obesity related comorbidities, amount of weight lost and the maintenance of the new weight play a crucial role. Based on several studies, bariatric surgery has been recognized as the most efficient way to lose weight as well as achieve remission from metabolic comorbidities compared to conservative methods. Much to our interest, both hypertension and chronic kidney disease can be alleviated as a result of bariatric surgery. Hence, in this study we wanted to assess whether the amount of RSF decreases after bariatric surgery and whether the change in the amount of RSF associates with remission from hypertension. The study population consisted of 74 patients with obesity and 46 lean control subjects. The groups were well-matched for age and sex. Both groups underwent broad metabolic blood sample analyses and MR-imaging. Patients with obesity were studied before and after bariatric surgery. The MRI data were analysed using a “single slice technique” as proposed by Foster et al. Renal function was evaluated with estimated GFR according to the EPI-CKD formula. This study resulted in several outcomes: First, patients with obesity accumulated more fat in the renal sinus compared to healthy lean individuals. Patients with hypertension also have larger RSF, compared to normotensive subjects and in the pooled data renal sinus fat correlates inversely with eGFR. Following bariatric surgery, RSF was decreased and patients who achieved hypertension remission had a larger decrease in RSF compared to patients who did not achieve remission. Finally, in patients with no hypertension remission, a larger decrease in RSF was associated with a decrease in the number of antihypertensive drugs used. The study results were in line with previous findings. We were able to demonstrate an association between RSF change and remission from hypertension, as well as the number of antihypertensive drugs needed. However, we could not show a direct link between RSF and blood pressure values, probably because of the masking effect of antihypertensive drugs used by patients with hypertension diagnosis. A significant strength of our study was our thorough assessment of MRI both pre and post bariatric surgery. Limitations of the present study were the relatively small study population and the greater number of women studied compared to men. Also, our analyses provided us with larger RSF areas than previously reported data which on the other hand did not seem to affect the main findings. In conclusion, we were able to add valuable information to the previously existing findings and thus support the theory suggesting the role of RSF in the pathogenesis of obesity related hypertension.